2014
DOI: 10.1097/01.epx.0000451827.84315.5c
|View full text |Cite
|
Sign up to set email alerts
|

Iron profile and dietary pattern of primary school obese Egyptian children

Abstract: The association between ID and obesity may have important public health and clinical implications. For primary school children with elevated BMIs, screening for ID should be considered. Increasing awareness of the importance of physical activity and carrying out nutritional education programs are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Meta-analysis revealed that having obesity doubled the odds of iron deficiency diagnosis (OR 2.1; 95% CI 1.4–3.2). However, the removal of one study 56 with a large effect size during sensitivity analysis reduced the association (OR 1.8; 95% CI 1.3–2.6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analysis revealed that having obesity doubled the odds of iron deficiency diagnosis (OR 2.1; 95% CI 1.4–3.2). However, the removal of one study 56 with a large effect size during sensitivity analysis reduced the association (OR 1.8; 95% CI 1.3–2.6).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 028 studies identified following database searches and de‐duplication, 41 met the inclusion criteria (Figure 1). These studies presented results investigating relationships between childhood obesity and five distinct health outcomes: asthma ( n = 16), 31–45 vitamin D deficiency ( n = 10), 46–55 iron deficiency ( n = 10), 34,56–64 flat‐footedness/pes planus ( n = 4) 65–68 and allergies ( n = 4) 34,39,69,70 . Two of the studies identified reported results for more than one of the outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in favour of a direct relationship between VA status (n=10 of 17 studies, accounting for 19 443 participants), 5 found an inverse association and 2 found no association (figure 4C). In the 10 studies that found a direct relationship, these were reported in a variety of ways, such as, lower risk of VAD in the context of overweight or obese75 79–83 or elevated serum levels of VA or plasma retinol in children with overweight or obesity 73 84–86. Interestingly, of the five studies that concluded an inverse association between overnutrition and VA deficiency, four focused on Brazilian children.…”
Section: Resultsmentioning
confidence: 99%
“…Although in favour of a direct relationship between vitamin A status (n=10 of 17 studies, accounting for 19,443 participants), 5 found an inverse association and 2 found no association ( Figure 4C ). In the 10 studies that found a direct relationship, these were reported in a variety of ways, such as: lower risk of VAD in the context of overweight or obese 69 7377 , or elevated serum levels of vitamin A or plasma retinol in children with overweight or obesity 67 7880 . Interestingly, of the 5 studies that concluded an inverse association between overnutrition and vitamin A deficiency, 4 focused on Brazilian children.…”
Section: Resultsmentioning
confidence: 99%